The Role of Green Self-Identity and Self-Congruity in Sustainable Food Consumption Behaviour - Gravelines, Žaneta; Banytė, Jūratė; Dovalienė, Aistė; Gadeikienė, Agnė (Organizations and Markets in Emerging Economies, 2022)
The aim of this paper is to explore the role of green self-identity and self-congruity with green food products in predicting consumers’ sustainable food consumption behaviour. Previous research suggests that there is a relationship between individuals’ self-identity and the consumption of products. However, when it comes to the realm of sustainable food consumption, those relations are not unambiguous. This study employs a survey with a sample of 837 respondents in Lithuania. The findings confirm that green self-identity and self-congruity with green food products positively influence subsequent sustainable food consumption behaviour both directly and indirectly. The implications of this study can be used to better understand green consumer behaviour and provide useful information to marketers and policymakers by suggesting that the promotion of sustainable food consumption behaviour should highlight not only functional but symbolic benefits as well.
Keywords: sustainability; sustainable food consumption; green self-identity; self-congruity with green food products